Myopericarditis - Richard Stair (Association of American Medical Colleges, 2010)
Abstract This simulation contains the case of a young, healthy man who presented to the emergency department with chest pain. The EKG appeared consistent with inferior infarction, and emergency department evaluation and management must address acute coronary syndrome (ACS) as a possibility. Ultimately, the patient was diagnosed as having myopericarditis. The decisions made should be supported by the available data, and though the age makes ACS less likely, the EKG appears consistent with inferior infarction and does not appear typical for pericarditis. The case has demonstrated students' and residents' reluctance to interpret EKG and intervene with young, healthy patients. This simulation has been used to teach both fourth-year medical students and emergency medicine residents clinical reasoning skills and decision making, EKG interpretations, and about myopericarditis specifically. It has been administered to residents at two different emergency medicine residency programs. Both sets of residents showed variability in executing the case, with some consulting cardiology early while some did not consult cardiology at all.